2014
DOI: 10.1185/03007995.2014.904771
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches for prophylactic cranial irradiation in extrapulmonary small cell carcinoma

Abstract: In the literature, the brain metastasis incidence of EPSCC might vary from 1.7% up to 40%. In many patients with ESPCC, PCI is not recommended. However, we have to keep in mind that primary head and neck and prostate SCC are exceptions due to the high incidence of cranial metastasis; PCI should be recommended for these patients on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
(52 reference statements)
0
13
0
5
Order By: Relevance
“…It remains unclear if the benefits of PCI in small cell lung cancer can be extrapolated to patients with small cell bladder cancer. Few of the published studies discussing PCI in extrapulmonary small cell have included primary bladder tumors, (8, 13-17) the largest documented series citing only 3 patients (2). Most have discouraged the use of PCI in this population as the incidence of brain metastases is thought to be as low as 5 – 18% (2, 8, 9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear if the benefits of PCI in small cell lung cancer can be extrapolated to patients with small cell bladder cancer. Few of the published studies discussing PCI in extrapulmonary small cell have included primary bladder tumors, (8, 13-17) the largest documented series citing only 3 patients (2). Most have discouraged the use of PCI in this population as the incidence of brain metastases is thought to be as low as 5 – 18% (2, 8, 9).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, PCI has become a standard of care in some patients with small cell cancer of the lung. However, it is unclear if the same survival benefit of PCI extends to patients with extrapulmonary small cell carcinoma, where the reported incidence of brain metastases is only 5 – 18% (2, 8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…The literature remains controversial regarding giving PCI to patients with small cell carcinoma of the head and neck. Yacizi suggested that since extrapulmonary primary small cell carcinoma in the head and neck region have a high incidence of brain metastasis at 41%, PCI should be considered for these patients [ 14 ]. While Mason suggests that brain metastases are rare for these patients and prophylactic cranial irradiation is not warranted [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…For small cell lung cancer (SCLC) the addition of prophylactic cranial irradiation (PCI) to the treatment leads to both a significant risk reduction of brain metastases and prolonged survival [3] . The risk of haematogenous metastases from small cell head and neck cancer is lower than that of SCLC, yet still significant, and PCI has been recommended for selected cases of small cell head and neck cancer [2] , [4] , [5] , [6] , [7] . Adding PCI after radiotherapy for sinonasal cancer is sub-optimal from a dosimetric point of view, as some areas of the brain already received a radiation dose from the primary tumour irradiation, that may cause late side effects, and probably has a low effect on tumour cells, as the dose per fraction is very low.…”
Section: Introductionmentioning
confidence: 99%